INTRODUCTION OF DRUG INFORMATION FROM DRUG PACKAGING AND LABELS IN THE COMMUNITY OF CIKULUR SERANG BANTEN - Nurliana, Lia; ., Sucihati; Adha, Suhroji; Nurhikmat, Mira; ., Annissa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Indonesian society today has become accustomed to the use of drugs. This can be caused by various factors such as the development of the disease, the production of various types of drugs and supplements, in addition to the large number of pharmacies that sell drugs that do not follow the applicable rules and the start of the implementation of national health insurance such as BPJS has allowed people to get easier access to treatment. These developments have caused various positive and negative impacts. The positive impact that can be seen is that more and more people are starting to care about health by checking themselves into healthcare places. While the negative impact that may arise with the increasing use of drugs in the community is errors in using drugs. This can occur due to a lack of knowledge and information conveyed to the public regarding the use of good and correct drugs. Errors in the use of drugs can cause harm both to society and to the environment. This counseling activity is intended for the community to increase basic knowledge of drugs, namely recognizing drug signs and etiquette (labels) useful for reducing drug abuse and increasing insight into drugs on the market.